The threat of the 'returning foreign fighter': The securitization of EU migration and border control policy. (October 2019) - Baker-Beall, Christopher
This article analyses the European Union's response to the threat of the 'returning foreign fighter' (referred to with increasing frequency as the 'foreign terrorist fighter'), arguing that it has been characterized by a move to (re)frame migration and border control as essential aspects of EU counter-terrorism policy. The article offers three important observations on the significance of this move. First, it critiques the way in which the EU's response to this problem is based upon and reinforces a narrow understanding of returning foreign fighters. Second, it argues that the EU has invoked the threat from returning foreign fighters not with the sole intention of preventing terrorism but rather as part of the ongoing securitization of migration and the EU border. Third, it suggests that the threat from returning foreign fighters has been invoked as a way of further legitimizing the EU's emerging role as a security actor and its embrace of preemptive security practice. The article argues throughout that the move to construct the returning foreign fighter issue in this way has important political and social implications for all categories of migrant, with migrant populations now deemed a potential source of terrorist threat.